What does it cost to improve household diets in Nepal? Using the cost of the diet method to model lowest cost dietary changes - Biehl, E.; Klemm, R.D.; Manohar, Swetha; Webb, Patrick; Gauchan, D.; West, K.P. (SAGE Publications, 2016)
In Nepal, limited availability and affordability of nutritious foods contribute to malnutrition.To identify nutrient deficiencies in commonly consumed diets and model lowest cost changes that could improve diet quality in 3 agroecological zones of Nepal.In August to September 2014, we collected market price and women’s food frequency data from 3 representative villages in Nepal’s mountains (Mahat Gaun, Jumla, n = 181 households), hills (Sitapur, Arghakhanchi, n = 166), and terai (Saigaun, Banke, n = 232) and verified local diets during women’s group discussions. Using the Cost of the Diet method, we compared models of the most nutritious version of a commonly consumed diet given locally available foods (“common diet”) with the cheapest possible diet meeting nutrient requirements, including foods not currently available (“optimal diet”).The household common diet lacks sufficient vitamin B12, riboflavin, and calcium in the mountains; B6, B12, calcium, and iron in the hills; vitamin A, calcium, and iron in the terai. Adding fish to the mountain and hill diets and increasing dark green leafy vegetable consumption in all zones yielded nutritional adequacy. Optimal diets are more expensive than the common diet in the mountains and hills but less expensive in the terai.The modeled lowest cost diet commonly eaten in 3 Nepalese communities lacks key nutrients. Policies and interventions that increase market availability and consumption of vitamin B12- and calcium-rich fish and dark green leafy vegetables could improve local diets, particularly in the mountains and hills.